DISCOURSE, IDENTITY, AND RITUAL ROLES: PARTICIPANT DYNAMICS IN THE ANRONG BUNTING KARAENG WEDDING TRADITION OF JENEPONTO - Kasmawati, Kasmawati; Tajuddin, Maknun; A.B Takko, Bandung; Munira, Hasjim (Universitas PGRI Sumatera Barat, 2025)
This study investigates the role of participants in the Anrong Bunting Karaeng ritual speechwithin the Jeneponto community’s wedding processions in South Sulawesi, Indonesia. Using an ethnographic approach framed by Duranti’s anthropological linguistics, the research analyzes ritual texts and performances from five ceremonial stages: Akbakra (yellow powder), Appasili (bridal bath), Akkrontigi (girlfriend night), Appantama Baju (wearing the wedding dress), and Appabajikang (uniting). Findings indicate two leading participant roles: internal participants encoded in the ritual texts through pronouns (e.g., proclitics ku- ‘I’, enclitics -na ‘he/she’, -nu ‘you’), and external participants comprising families, relatives, and guests. Beyond the grammatical functions, these pronouns construct social roles, hierarchies, and symbolic authority, with Anrong Bunting Karaeng serving as both animator and mediator between human and spiritual realms. The study highlights that ritual speech encodes power relations and collective identity, positioning participants as actors and carriers of cultural values. However, the analysis remains primarily descriptive; further research should integrate multimodal data (gesture, intonation, performance) and explore generational changes in ritual interpretation. This research contributes to anthropolinguistics by showing how ritual discourse preserves cultural identity while adapting to modernity. It also emphasizes the importance of documenting and analyzing local rituals to sustain intangible cultural heritage in Indonesia and beyond.